2013
DOI: 10.1155/2013/976765
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RASSF1A Expression in Colorectal Cancer and Its Association with K-ras Status

Abstract: Background. The RAS-association domain family 1 A (RASSF1A) is a classical member of RAS effectors regulating cell proliferation and apoptosis. Loss of RASSF1A expression may shift the balance towards a growth-promoting effect without the necessity of activating K-ras mutations. Its potential association with K-ras mutations in colorectal cancer (CRC) is unclear. Methods. RASSF1A expression was examined in normal mucosa, adenoma, and tumor tissues of colon and rectum, respectively. We examined the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 25 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Phosphorylation β loss of function in prostate cancer [119], CCL: overexpression inhibits cell proliferation and promote apoptosis in HepG2 cells [87] Mouse double KO: cholangiocarcinoma [46,101], HCC [120] Decreased mRNA level in tumour associated with node metastasis [121], mouse double KO: crypt dysplasia, colon adenoma [46,78,120] RASSF1, RASSF1A TSG: promoter hypermethylation and decrease expression in cancer: thyroid [122], oesophageal [123], prostate [124], colorectal, breast [125] TSG; promoter hypermethylation and decrease expression in CRC [126,127] SAV1, Salvador TSG: LOH and downregulation in renal cell carcinoma [128], no gene mutation in stomach, liver and lung cancer [129] CCL: overexpression induces apoptosis in MCF-7 cells [130] No gene mutation in CRC [129] LATS1 TSG: decrease expression in cancer: glioma [131], NSLC [132], sarcoma [133] and astrocytoma [134]. CCL: LATS1 degradation inhibits apoptosis in MCF10A cells [135] TSG: promoter hypermethylation and mRNA decrease in CRC [86] LATS2 TSG: decrease expression in: malignant mesothelioma (and LOH) [136], NSLC (no mutation found) [137] and astrocytoma [134] OG: overexpression in AML [138], nosopharyngeal carcinoma [139] TSG: downregulation in CRC [87] …”
Section: Stk4 Mst1 and Stk3 Mst2mentioning
confidence: 99%
“…Phosphorylation β loss of function in prostate cancer [119], CCL: overexpression inhibits cell proliferation and promote apoptosis in HepG2 cells [87] Mouse double KO: cholangiocarcinoma [46,101], HCC [120] Decreased mRNA level in tumour associated with node metastasis [121], mouse double KO: crypt dysplasia, colon adenoma [46,78,120] RASSF1, RASSF1A TSG: promoter hypermethylation and decrease expression in cancer: thyroid [122], oesophageal [123], prostate [124], colorectal, breast [125] TSG; promoter hypermethylation and decrease expression in CRC [126,127] SAV1, Salvador TSG: LOH and downregulation in renal cell carcinoma [128], no gene mutation in stomach, liver and lung cancer [129] CCL: overexpression induces apoptosis in MCF-7 cells [130] No gene mutation in CRC [129] LATS1 TSG: decrease expression in cancer: glioma [131], NSLC [132], sarcoma [133] and astrocytoma [134]. CCL: LATS1 degradation inhibits apoptosis in MCF10A cells [135] TSG: promoter hypermethylation and mRNA decrease in CRC [86] LATS2 TSG: decrease expression in: malignant mesothelioma (and LOH) [136], NSLC (no mutation found) [137] and astrocytoma [134] OG: overexpression in AML [138], nosopharyngeal carcinoma [139] TSG: downregulation in CRC [87] …”
Section: Stk4 Mst1 and Stk3 Mst2mentioning
confidence: 99%
“…Hypermethylation of RASSF1A was also frequently found in early flat type colorectal tumors, characterized by high‐grade dysplasia from early small flat mucosal lesion and exhibited more aggressive behavior. More recently, RASSF1A methylation has also been reported to occur in advanced cancer and associate with distant metastasis . It indicates that RASSF1A methylation may involve in tumor metastasis and invasion of CRC.…”
Section: Discussionmentioning
confidence: 96%
“…This absence of RASSF1A expression was more frequently observed in the presence of wild‐type KRAS. These results suggested that the inactivation of RASSF1A is a complementary mechanism during the onset of CRC in addition to K‐Ras mutation . Although the exact mechanism of RASSF1A functioning as an RAS effector is not clear, the mutually exclusive relationship between RASSF1A and KRAS mutation specifies that RASSF1A can serve as a therapeutic predictive factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of Ras with RASSF1A promotes the activation of the MST kinases and therefore Hippo pathway activation, leading to down-regulation of YAP. Many tumors exhibit loss of RASSF1A expression [126,261], thus uncoupling Ras from Hippo and facilitating transformation. NORE1A, like RASSF1A, is a RASSF family member that serves as a direct, proapoptotic Ras effector [10,11].…”
Section: -Discussionmentioning
confidence: 99%